¿Podemos escuchar a la naturaleza? La naturaleza como víctima y testigo en el Informe final de la Comisión de la Verdad en Colombia - Andrés Villegas; Catalina Castrillón Gallego (Revista de Estudios Sociales)
Drawing on the premises of the ontological turn, this article explores the recognition of nature as both a victim and a witness to the Colombian armed conflict, as framed by the Commission for the Clarification of Truth, Coexistence, and Non- Repetition. The analysis is based on an in-depth review of the report When the Birds Did Not Sing, supplemented by an examination of other volumes of the Truth Commission’s Final Report and its extensive supplementary materials. It also incorporates transcripts of numerous testimonies collected by the Commission and rulings from other institutions that recognize nature or territory as subjects of rights and as victims. The findings reveal that the Commission adopted no singular understanding of nature. Among the multiple interpretations it offers, the most compelling considers nature as a witness to the harm inflicted upon it. This perspective is rooted in (i) the relational ontologies of campesino, Indigenous, and Afro-Colombian communities who testified; (ii) the political dimension of these ontologies, which positions harm and reparation as contested and negotiable within worlds that are “more than one and less than many”; and (iii) the notion that nature itself testifies, as the production and interpretation of signs is an inherent property of life. Ultimately, the article argues that the Commission shifts the question from “Can nature speak?” to “Can we listen to it?”